DYNAMICS AND COLOR CHARACTERISTICS OF CLASSICAL POPULATION OF TRANS NEPTUNIAN OBJECTS - Arwa Muhammad, Ghifari
Population of classical Trans-Neptunian Objects (TNOs), known as Cubewanos, resides beyond the orbit of Neptune and they are not in orbital resonances with Neptune and also not eccentric (eccentricity < 0.24). The Cubewanos are divided into two sub populations, i.e. Hot and Cold (separated at inclination ? 6?). The relationship between the separation with respect to inclination and colors of Cubewanos is still an unsolved problem. Study about the Cubewanos reveals understanding about the evolution of the Solar System and conditions of TNOs region. Report of this final project describes results of the orbital evolution of the Cubewano based on numerical integrations over a million years and its analyses, especially, with respect to the inclination and eccentricity. Additionally, color corrections of Cubewanos by possible extinction of interplanetary medium are examined. Color data are taken from the NASA Planetary Data System, while the JPL Small Body Database provides the orbital data. Some orbital phenomena happen after a million years numerical integration. These include changes in the eccentricity of Cubewano orbits, which result in objects no longer being classified as Cubewanos, and change over the inclination values exchange Cubewanos from their previous sub populations. Moreover, Kozai resonance may be observed in some cases. There are also objects with chaotic orbits that, after a million years, show high inclinations and high eccentricities. This suggests that in the future, those objects will be ejected from TNOs region. The color corrections, which decrease as the inclination increase, take place of 2.25 – 3.72 % in the ecliptic and lessen at higher inclinations.